2012
DOI: 10.1016/j.eurpsy.2012.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversity and psychosis: Examining whether the association is due to genetic confounding using a monozygotic twin differences approach

Abstract: 140 Word count of text: 4279Number of tables/figures: 2 3 Abstract Purpose: To test whether the association between childhood adversity and positive and negative psychotic experiences is due to genetic confounding. Method:Childhood adversity and psychotic experiences were assessed in a sample of 226 twins from the general population. A monozygotic (MZ) twin differences approach was used to assess possible genetic confounding. Results:In the whole sample, childhood adversity was significantly associated with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 46 publications
5
43
0
1
Order By: Relevance
“…This is consistent with an earlier adoption study reporting that severe institutional deprivation can cause inattention/overactivity symptoms (148) and with similar findings for other psychiatric conditions (190,191). Vulnerability for ADHD symptoms could result from alterations in neural pathways involved in working memory, executive and emotional control (152,153,192) following maltreatment.…”
Section: Can Environmental Risks Causally Contribute To Adhd?supporting
confidence: 80%
“…This is consistent with an earlier adoption study reporting that severe institutional deprivation can cause inattention/overactivity symptoms (148) and with similar findings for other psychiatric conditions (190,191). Vulnerability for ADHD symptoms could result from alterations in neural pathways involved in working memory, executive and emotional control (152,153,192) following maltreatment.…”
Section: Can Environmental Risks Causally Contribute To Adhd?supporting
confidence: 80%
“…While experimental studies on humans aimed at establishing causation are not an ethical option, there are recent findings from a study of monozygotic (MZ) twins that are relevant to this issue. Using the MZ twin differences approach, investigators obtained data on childhood adversity and subclinical “psychotic experiences” from both members of the twin pairs (Alemany et al, 2012). They found that within-pair twin differences in exposure to childhood adversity were significantly associated with corresponding differences in subclinical positive symptoms, suggesting that the relation between childhood adversity and symptoms is not solely attributable to genetically determined differences in vulnerability.…”
Section: Psychosocial Stress and The Prodromementioning
confidence: 99%
“…All of these studies 7,19,20 reported strong and significant associations between childhood adversity and psychosis, even when controlling for genetic risk. These studies thus suggest that, even if we assume that genetic risk for psychosis increases the likelihood of exposure to CT, the actual exposure in itself further increases the risk for psychosis.…”
Section: Evidence For Associationmentioning
confidence: 99%